Learning how to swim in 5- to 12-year-old children: a scoping review of evidence-based motor learning methods - Minkels, Carola; van der Kamp, John; de Vries, Ralph; Beek, Peter J. (Frontiers in Sports and Active Living, 2025)
BackgroundSwimming is widely acknowledged for its safety and health benefits. Across the world children are receiving swimming lessons in which a variety of learning methods are employed. However, little is known about the effectiveness of those methods, and a comprehensive overview of pertinent research is lacking. Such an overview is needed for both researchers and instructors seeking to improve swimming skill acquisition in children.ObjectiveThis scoping review aims to provide an overview of studies examining the effectiveness of motor learning methods for the acquisition of swimming skills by 5- to 12-year-old children, including an evaluation of their theoretical underpinnings, methodological quality, and core findings.MethodsThis scoping review adhered to the PRISMA guidelines and followed Tricco et al.'s framework for conducting and reporting scoping reviews. Five bibliographic databases were systematically searched. Peer-reviewed studies in all languages published before 2025 were considered. Studies focusing on children with water-related fear were included. Gray literature, non-peer-reviewed studies and studies on specific groups (e.g., young, competitive swimmers or children with disabilities), or cognitive/motivational outcomes were excluded. Review selection and characterization were performed by three independent reviewers using pretested forms.ResultsA total of 23 studies were included, which were classified into three main categories: traditional motor learning methods (n = 4), contemporary methods (n = 1), and atheoretical methods (n = 18). Traditional methods focused on video-based instruction and feedback (n = 4). Contemporary methods involved a single study on a non-linear swimming program (n = 1). Atheoretical methods were further classified into learn-to-swim programs (n = 12), learning environments (n = 3), and assistive devices (n = 3). Most studies (87%) reported a positive effect of the motor learning method under investigation during practice. However, significant methodological limitations were identified. Specifically, 87% of studies did not incorporate retention or transfer tests, 35% lacked control or comparison groups, and 48% did not provide detailed descriptions of the investigated intervention(s). Additionally, 83% of studies were not explicitly grounded in theoretical frameworks, except for the video-based studies and the study on a non-linear swimming program.ConclusionThe literature on this topic is scarce, generally atheoretical and of questionable methodological quality. Addressing these shortcomings in future research will improve the evidence-base for the effectiveness of theoretically inspired learning methods for the acquisition of swimming skills in children, and their long-term retention and transfer, which in turn might result in evidence-based innovations in swimming lessons.Systematic Review RegistrationPRISMA (RRID:SCR_018721).